2021
DOI: 10.1016/j.radcr.2021.06.089
|View full text |Cite
|
Sign up to set email alerts
|

Atypical imaging presentation of a massive intracavitary cardiac thrombus: A case report and brief review of the literature

Abstract: Intracavitary cardiac thrombi, uncommonly found in the right chambers, have been shown to form secondary to endocardial and myocardial diseases. The differential diagnosis for an intracavitary cardiac mass is broad, including primary cardiac tumors, cardiac metastases, anatomic variants, vegetations, and thrombi. Here we present a unique case with a large calcified intracavitary cardiac thrombus in a 26-year-old woman with obesity, immune thrombocytopenic purpura, and a new diagnosis of systemic lupus erythema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The INARI FlowTriever device can remove DVT and significantly reduce the risk of bleeding [ 14 ]. Some studies analyzed and studied the causes of DVT and the locations where DVT frequently occurs [ 15 , 16 ]. Other studies have found that DVT can trigger other diseases [ 2 , 17 19 ], such as multiple organ embolism, stroke, and acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The INARI FlowTriever device can remove DVT and significantly reduce the risk of bleeding [ 14 ]. Some studies analyzed and studied the causes of DVT and the locations where DVT frequently occurs [ 15 , 16 ]. Other studies have found that DVT can trigger other diseases [ 2 , 17 19 ], such as multiple organ embolism, stroke, and acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The improved spatial and temporal resolution of imaging modalities have led to increased detection of normal anatomical variants and structures, which may lead to misdiagnosis. Hence, a comprehensive understanding of normal anatomical variants, and its characteristic appearance on transthoracic echocardiogram, CT and PET/CT is essential [ 1 , 3 , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, normal variants are typically distinguished from masses based on their location and ancillary features (including: attenuation values, contrast enhancement and local invasion). Delayed phase (45–60 seconds) can help in differentiating intracavitary thrombus from normal variants [ 9 , 15 , 16 , 19 , 20 ]. Thrombus would remain low attenuating, whereas normal variants will show contrast enhancement similar to adjacent myocardium [ 1 , 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathology in the mediastinum typically originate from lymph nodes, thymus, thyroid, esophagus, neurogenic, vascular and germ cell tumor [20] . Rare etiology would include amyloidosis or cardiac mass extending into the mediastinum [21] , [22] , [23] , [24] . Intrapulmonary bronchial artery aneurysm presents with hemoptysis when ruptured into the trachea or airways.…”
Section: Discussionmentioning
confidence: 99%